PERSEPSI GURU SEKOLAH DASAR TERHADAP PENERAPAN KURIKULUM MERDEKA DALAM KEGIATAN PEMBELAJARAN: STUDI KUALITATIF DESKRIPTIF BERBASIS KAJIAN LITERATUR - Farahul Phadiyah Zuandi; Elfia Sukma; Inggria Kharisma (STKIP Subang, 2026)
This study aims to describe elementary school teachers’ perceptions of the implementation of the Merdeka Curriculum in learning activities based on a literature review. This research used a descriptive qualitative approach with a library research method. The data were obtained from 15 scientific journal articles related to elementary school teachers’ perceptions, Merdeka Curriculum implementation, teacher readiness, assessment, differentiated learning, IPAS, and the Pancasila Student Profile Strengthening Project. The data were analyzed using content analysis by reviewing the objectives, methods, findings, and discussions of each article, then grouping the findings into several main themes. The results show that elementary school teachers generally have positive perceptions of the implementation of the Merdeka Curriculum. Teachers view this curriculum as providing broader space to choose teaching methods, learning materials, media, and learning activities that suit students’ needs and characteristics. The Merdeka Curriculum is also considered capable of encouraging more active, flexible, and meaningful learning. Nevertheless, its implementation still faces several obstacles, such as uneven teacher understanding, difficulties in preparing teaching modules, assessment implementation, differentiated learning, P5, limited facilities, and the need for more continuous mentoring. The successful implementation of the Merdeka Curriculum in elementary schools is strongly influenced by teacher readiness, school support, the availability of teaching resources, and teachers’ ability to adjust learning to students’ real conditions.